2015
DOI: 10.1111/cfs.12222
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of youth resilience across seven South African sites

Abstract: Child and Family Social Work 201 , 2 , pp -22 7 2 226 235 5 8 A comparison of youth resilience in South Africa A D van Breda Child and Family Social Work 201 , 2 , pp -22 7 2 226 235 5 9 A comparison of youth resilience in South Africa A D van Breda

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Studies have observed that in spite of difficult situations, some young care‐leavers are able to overcome such barriers and lead a successful life. They are able to recover from their vulnerabilities and are more resilient (Stein, ; Van Breda, a). Cases have been documented of similar stable environments for growth and development, in which some were unable to adjust and suffered from unresolved trauma, feelings of isolation, and emotional instability, while others performed much better (Mendes, Pinkerton & Munro, ).…”
Section: Factors Affecting Transition Out Of Carementioning
confidence: 99%
“…Studies have observed that in spite of difficult situations, some young care‐leavers are able to overcome such barriers and lead a successful life. They are able to recover from their vulnerabilities and are more resilient (Stein, ; Van Breda, a). Cases have been documented of similar stable environments for growth and development, in which some were unable to adjust and suffered from unresolved trauma, feelings of isolation, and emotional instability, while others performed much better (Mendes, Pinkerton & Munro, ).…”
Section: Factors Affecting Transition Out Of Carementioning
confidence: 99%
“…A growing number of resilience researchers from countries in the Northern Hemisphere (e.g., the United Kingdom, Canada, the United States) endorse an ecological systems approach to explain how and why young people adjust well to chronic or acute stressors that predict negative life outcomes (Cicchetti, 2013;Masten, 2001;Panter-Brick, 2015;Rutter, 2013;Ungar, 2011;Wright & Masten, 2015). There is a similar tendency among resilience-focused researchers from countries in the Southern Hemisphere (e.g., South Africa, Colombia, New Zealand; e.g., Bottrell, 2009;Montoya, Restrepo, Duque, & Ungar, 2011;Sanders & Munford, 2014;Theron, 2015;van Breda, 2015). Implicit in this global endorsement is recognition that resilience is a process that (i) shows variation across developmental stages and historic time, sociocultural contexts, type of adversity, and demographic factors and (ii) draws on multiple systems, from molecular through to family, community, and even the physical environment.…”
mentioning
confidence: 99%
“…Luthar, Cicchetti, and Becker define resilience as "a dynamic process encompassing adaptation within the context of significant adversity" (Luthar, Cicchetti, & Becker, 2000, p. 1). "In studies of disadvantaged children, resilience is typically present when (a) children living in conditions of risk (b) show better-than-predicted outcomes (c) presumably due to some intervening process" (Breda, 2017;Smokowski, Reynolds, & Bezruczko, 1999, p. 426). The American Psychological Association emphasizes resilience as a trait anyone can learn and develop (American Psychological Association, 2018).…”
mentioning
confidence: 99%